Pengaruh Penggunaan Media Educaplay Terhadap Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar - Fitri Dian; Depi Prihamdani; Harmawati (Jurnal Educatio FKIP UNMA, 2026)
This study is grounded in the low learning outcomes of Natural and Social Sciences (IPAS), among fifth-grade students at SDN Sumurlaban I, which are influenced by conventional instructional practices and limited utilization of technology-based media. The objective of this study is to examine the effect of using Educaplay media on IPAS learning outcomes of fifth-grade elementary school students. A quantitative approach was employed in this research using a quasi-experimental method with a One Group Pretest-Posttest Design. Data collection was conducted through pretest and posttest, while data analysis utilized descriptive statistics, normality testing, and paired sample t-test assisted by IBM SPSS on the material “My Regional Cultural Heritage”. Findings indicated an increase in the mean score from 47.71 in the pretest to 75.63 in the posttest. The normality test results showed a significance value greater than 0.05, indicating that the data were normally distributed. The paired sample t-test results obtained a significance value of less than 0.001, leading to the rejection of H₀ and acceptance of Hₐ. in the tested learning context.